2018
DOI: 10.1111/psyg.12381
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activity and life satisfaction in older adults

Abstract: Aim Based on the concept of successful ageing and research reports on the benefits of maintaining sexual activity in mid‐ to late life, the purpose of the current study was to examine the relationship between global life satisfaction and sexual satisfaction in adults older than 60 years. The study also analyzed the relationship between various forms of sexual activity (genital and non‐genital) and both types of satisfaction. Methods Thirty‐three men and 50 women (N =83) were interviewed by using two structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 19 publications
4
36
0
Order By: Relevance
“…they place greater emphasis on activities such as kissing, hugging or touching another person. On the other hand, younger people usually refer to their sexual well-being based on their perceived sexual satisfaction (Gott & Hinchliff, 2003;Skałacka & Gerymski, 2019;Watson et al, 2017). Touching, kissing and cuddling seem to be more mature and subtle forms of sexuality expression, which are not directly identified with sexual well-being, but are certainly a part of it.…”
Section: mentioning
confidence: 99%
“…they place greater emphasis on activities such as kissing, hugging or touching another person. On the other hand, younger people usually refer to their sexual well-being based on their perceived sexual satisfaction (Gott & Hinchliff, 2003;Skałacka & Gerymski, 2019;Watson et al, 2017). Touching, kissing and cuddling seem to be more mature and subtle forms of sexuality expression, which are not directly identified with sexual well-being, but are certainly a part of it.…”
Section: mentioning
confidence: 99%
“…Sexual satisfaction is a good predictor of global life satisfaction in young people and older adults [ 26 ]. In a large survey on sexual health in Spain [ 27 ], people were interviewed about their motivation for sexual intercourse, and the vast majority pointed out that the main reason was either the search for emotional intimacy or to satisfy the need to love and be loved.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that sexuality plays an essential role for all age groups, including the elderly population, and can be considered as a cornerstone of global life satisfaction (Morton, 2017;Skałacka & Gerymski, 2019). Cancer diagnosis and related treatments have a detrimental effect on sexual function (Schover, 2005;Stanton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%